REDESAIN KEMASAN TUSUK TUSUK KUNTI - MIFTAHUR RAHMAH MASRIL, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The existing Tusuk Tusuk Kunti packaging design is not safe for taking away and it could not keep the food quality, information about the product was not available, and the old design had not been a good promotion media yet.Tusuk Tusuk Kunti packaging design which is more communicative, more interesting, and safer will be able to present message from Tusuk Tusuk Kunti. The purpose of this design is to introduce Tusuk Tusuk Kunti identity to people and being a good promotion media for reaching a larger trade.The analysis method used in this design is SWOT (strength, weakness, opportunity, threats) analysis to find the solution from the problem encountered. Designing process starts from data collection, observation, and documentation to collect the data and observe directly without participating in the production from the beginning to the final. Supporting media to support main media are poster, apron, sticker, x-banner, t-shirt, menu list and banner.Keywords: Redesign, packaging, food, snacks.